Uji Ekstrak Etanol Pakkat Terhadap Gambaran Histopatologi Pankreas Tikus Wistar Jantan Yang Diinduksi Aloksan - Roland Daniel Theodore Amudi Matondang; Aleksander Marganda Sidebang; Yolanda Eliza Putri Lubis; Maya Sari Mutia; Stevenie - (PRIMER (Prima Medical Journal), 2023)
Objective: This take a look at ambitions to study the effectiveness of pakkat extract on the histopathological functions of the pancreas of male Wistar rats (Rattus novergicus) prompted with the aid of alloxan. methods: The layout used was an experimental layout with a pre-take a look at and publish-check randomized manipulate layout, the pattern used became 25 hyperglycemic rats divided into 5 groups: terrible manage (given NaCMC), high quality control (metformin), remedy 1 ( pakkat extract 125 mg/weight), remedy 2 (packkat extract 250 mg/ weight), treatment 3 (packkat extract 500 mg/weight) for 14 days. outcomes: The outcomes showed that pakkat extract (Calamus caesius blume) with tracking doses of one hundred twenty five mg/weight and 250 mg/weight for 14 days continuously ought to lessen the advent of alloxan-caused damage to the pancreas of male Wistar rats, which became characterized with the aid of reduced cellular look. infection, decreased interstitial bleeding, and reduced vascular congestion. conclusion: Pakkat extract (Calamus caesius blume) in positive doses can repair the harm to the structure of histopathological picture in male Wistar rats prompted via alloxan with the finest dose of 250 mg/weight.